Waterlogging risk assessment for winter wheat using multi-source data in the middle and lower reaches of Yangtze River - Chen, Yuanyuan; Huang, Jingfeng; Song, Xiaodong; Wu, Hongyan; Sheng, Shaoxue; Liu, Zhixiong; Wang, Xiuzhen (International Journal of Agricultural and Biological Engineering, 2018)
Waterlogging is a serious agro-meteorological disaster caused by excessive soil water, which usually causes tremendous crop yield losses. The region of middle and lower reaches of Yangtze River in China is an important production base of winter wheat, and is an area prone to waterlogging. The risk assessment of winter wheat waterlogging can provide more thorough understanding about the risk-prone environment related with food safety in this region. This study combined a variety of environmental and agricultural factors and assessed the waterlogging risk of winter wheat from the aspects of sensitivity of hazard formative environments, hazard risk, and vulnerability of hazard-affected body using multi-source data. Furthermore, it constructed a compound waterlogging risk assessment model to classify the study area into high, relatively high, moderate, and low risky areas, respectively. The results showed that the proposed model could more comprehensively reflect the occurrence mechanism of winter wheat waterlogging by synchronizing geographical, agricultural, and meteorological factors. The waterlogging regionalization based on the model could reasonably represent the spatial distribution and differentiate regional characteristics of winter wheat waterlogging in the study area. Keywords: waterlogging, hazard formative environments, vulnerability, risk assessment DOI: 10.25165/j.ijabe.20181105.3246 Citation: Chen Y Y, Huang J F, Song X D, Wu H Y, Sheng S X, Liu Z X, et al. Waterlogging risk assessment for winter wheat using multi-source data in the middle and lower reaches of Yangtze River. Int J Agric & Biol Eng, 2018; 11(5): 198–205.